Menakar Kepuasan Mahasiswa: Peran Kualitas Sistem dan Konten Lokal Repository Usaktiana - Safitri, Dini; Hak, Ade Abdul (LIBTECH: LIBRARY AND INFORMATION SCIENCE JOURNAL, 2025)
The use of institutional repositories as part of digital library information systems has become essential in supporting access to academic resources in higher education. The Usaktiana Repository, developed by Trisakti University, is expected to assist final-year students in finding and using undergraduate thesis references more effectively. However, several issues related to system performance and content quality have impacted the user experience. This research seeks to examine how system quality and local content quality impact the satisfaction of final-year students from the Faculty of Law at Trisakti University in utilizing the Usaktiana Repository. A quantitative method was employed through a survey involving 91 participants. The study adopted the DeLone and McLean Information System Success Model as a conceptual framework to evaluate the effectiveness of the academic information system. The findings from the regression analysis indicate that system quality and local content quality each have a positive and significant influence on user satisfaction, both when examined separately and together. The coefficient of determination (R Square) value of 46.4% indicates that the combination of the two variables explains nearly half of the variation in user satisfaction. Partial contribution analysis shows that local content quality has a greater influence than system quality. These findings suggest that students prioritize access to relevant, high-quality academic content over technical system features. Therefore, developing a digital repository requires an integrated approach that emphasizes both reliable system performance and the availability of high-quality local academic content.